Quantifying multiple Permian–Recent exhumation events during the break‐up of eastern Gondwana: sonic transit time analysis of the central and southern Perth Basin. (18th May 2015) - Olierook, Hugo K. H.; Timms, Nicholas E.
Abstract: The central and southern Perth Basin in southwestern Australia has a geological history involving multiple regional unconformity‐forming events from the Permian to Recent. This study uses sonic transit time analysis to quantify the magnitudes of net and gross exhumation for four stratigraphic periods from 43 wells. Most importantly, we quantify gross exhumation of the Permian–Triassic, Triassic–Jurassic, Valanginian break‐up and post‐Early Cretaceous events. Post‐Early Cretaceous gross exhumation averages 900‐m offshore and 600‐m onshore. Up to 200 m of this exhumation may be attributed to localized fault block rotation during extension in the Late Cretaceous and/or reverse fault re‐activation due to the compressive stresses in Australia in the last 50 Ma. The remainder is attributed to regional exhumation caused by epeirogenic processes either during the Cenozoic or at the Aptian–Albian boundary. Maximum burial depths prior to the Valanginian unconformity‐forming event were less than those reached subsequently, so that the magnitude of Valanginian break‐up exhumation cannot be accurately quantified. Gross exhumation prior to the break‐up of Gondwana was defined by large magnitude differences (up to 2500 m) between adjoining sub‐basins. At the end of Triassic, exhumation is primarily attributed to reverse re‐activation of faults that were driven by short‐wavelength inversion and exhumation at the end Permian is likely caused by uplift of rotated fault blocks during extension. The evidence from quantitative exhumation analysis indicates a switch in regime, from locally heterogeneous before break‐up to more regionally homogeneous after break‐up.